Preliminary phylogeny of Fordiophyton (Melastomataceae), with the description of two new species - Zeng, Si-Jin; Zou, Long-Hai; Wang, Pan; Hong, Wen-Jun; Zhang, Guo-Qiang; Chen, Li-Jun; Zhuang, Xue-Ying (Phytotaxa, 2016)
A preliminary phylogeny of Fordiophyton (Melastomataceae) and the description of two new taxa, F. chenii and F. huizhouense, from southern China, are presented here. The phylogenetic analyses indicate that Fordiophyton is monophyletic and the two new species are in this clade of Sonerileae. Fordiophyton chenii is morphologically similar to F. cordifolium. Both taxa have glabrous stems, large, cordate leaves and four-sided petioles, but F. chenii has a very short stem, rosette leaves, hypanthia with dense glandular trichomes, and the shorter stamens with yellow anthers. Fordiophyton huizhouense shares with F. peperomiifolium the short, densely hirsute stem and rosette leaves, but F. huizhouense is characterized by adaxially smooth leaves, lanceolate calyx lobes, and inflated, prolonged connective bases in the longer stamens.